Molecular design and structural optimization of nanocellulose-based films fabricated via regioselective functionalization for flexible electronics - Dias, Otavio Augusto Titton; Konar, Samir; Pakharenko, Viktoriya; Graziano, Antimo; Leão, Alcides Lopes [UNESP]; Tjong, Jimi; Jaffer, Shaffiq; Cui, Teng; Filleter, Tobin; Sain, Mohini (Elsevier, 2022)
Nanocellulose backbones highly regioselectively substituted with thiophene and long fatty acid side chains were synthesized via a protecting group strategy. The presence of long-chain pendants balanced the torsional conformations of the nanocellulose backbone caused by large thiophene molecules on the nanostructured substrate, imparting enhanced electrical conductivity to the nanomaterial. The formation of a percolation network provided a conduction path and reinforcing effects enhancing energy transfer. The fabricated strong, flexible, and conductive regioselectively nanofibrillated cellulose-based films were demonstrated to be a potential alternative to conventional semiconductors. Optimization of the structure of nanocellulose backbones resulted in higher interaction between the active moieties and demonstrated higher electrical conductivity (279.10 μS/cm) when compared to randomly functionalized nanocellulose (65.05 μS/cm). The molecular design of the structures of nanocellulose may allow the fabrication of materials with consistent and reproducible properties. The well-defined architecture of functionalized nanostructures is an important step toward acceptance of nanocellulose as a bio- component in advanced materials.
Keywords: Cellulose nanofibrils; Conductivity; Conformation; Molecular dynamics; Polythiophene; Regioselective modification; Thiophene